Metabolic profile of puerarin in rats after intragastric administration of puerarin solid lipid nanoparticles - Luo CF (Dove Medical Press, 2013)
Cheng-Feng Luo,1,2 Ning Hou,2,3 Juan Tian,1,2 Mu Yuan,2,3 Shi-Ming Liu,1,2 Long-Gen Xiong,1,2 Jian-Dong Luo,2,3 Min-Sheng Chen1,2,41The Second Affiliated Hospital of Guangzhou Medical University, Guangzhou, People's Republic of China; 2Guangzhou Institute of Cardiovascular Disease, Guangzhou, People's Republic of China; 3Guangzhou Medical University, Guangzhou, People's Republic of China; 4Southern Medical University, Guangzhou, People's Republic of ChinaAbstract: Puerarin has multiple pharmacological effects and is widely prescribed for patients with cardiovascular diseases including hypertension, cerebral ischemia, myocardial ischemia, diabetes mellitus, and arteriosclerosis. We have successfully prepared puerarin-loaded solid lipid nanoparticles (Pue-SLNs) for oral administration. Pue-SLNs are prepared using monostearin, soya lecithin, and poloxamer 188. SLNs may alter the course of puerarin absorption predominantly to and through lymphatic routes and regions, presumably following a transcellular path of lipid absorption, especially by enterocytes and polar epithelial cells of the intestine. The alteration of absorption might influence the metabolic profile of puerarin when incorporated into SLNs. In the present study, we investigated the metabolic profile of puerarin in rat plasma and urine using rapid resolution liquid chromatography–tandem mass spectrometry after a single-dose intragastric administration of Pue-SLNs in comparison with puerarin suspension. Two glucuronidated metabolites of puerarin, puerarin-4΄-O-glucuronide and puerarin-7-O-glucuronide, were detected in rat plasma and urine after intragastric administration of Pue-SLNs, with the latter acting as the major metabolite. Similar results were found in rat plasma and urine after intragastric administration of puerarin suspension. The results suggest that incorporation of puerarin into SLNs does not change either the position of glucuronidation or the metabolic pathway of puerarin in rats.Keywords: puerarin, solid lipid nanoparticles, metabolic profiling